Prevalence of amblyopia and patterns of refractive error in the amblyopic children of a tertiary eye care center of Nepal - Sapkota, K; Pirouzian, A; Matta, NS (Nepalese Journal of Ophthalmology, 2013)
Introduction: Refractive error is a common cause of amblyopia. Objective: To determine prevalence of amblyopia and the pattern and the types of refractive error in children with amblyopia in a tertiary eye hospital of Nepal. Materials and methods: A retrospective chart review of children diagnosed with amblyopia in the Nepal Eye Hospital (NEH) from July 2006 to June 2011 was conducted. Children of age 13+ or who had any ocular pathology were excluded. Cycloplegic refraction and an ophthalmological examination was performed for all children. The pattern of refractive error and the association between types of refractive error and types of amblyopia were determined. Results: Amblyopia was found in 0.7 % (440) of 62,633 children examined in NEH during this period. All the amblyopic eyes of the subjects had refractive error. Fifty-six percent (248) of the patients were male and the mean age was 7.74 ± 2.97 years. Anisometropia was the most common cause of amblyopia (p < 0.001). One third (29 %) of the subjects had bilateral amblyopia due to high ametropia. Forty percent of eyes had severe amblyopia with visual acuity of 20/120 or worse. About twothirds (59.2 %) of the eyes had astigmatism. Conclusion: The prevalence of amblyopia in the Nepal Eye Hospital is 0.7%. Anisometropia is the most common cause of amblyopia. Astigmatism is the most common types of refractive error in amblyopic eyes. Nepal J Ophthalmol 2013; 5(9):38-44 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7820